SOLITARY PHILLIPSASTREIDAE (RUGOSA) FROM THE LATE DEVONIAN OF EUROPE AND NORTHERN AFRICA - SCHROeDER, STEFAN (Journal of paleontology, 2005)
Macgeea is a cosmopolitan genus of Devonian rugose corals that includes numerous, generally highly variable, species. Because of its wide skeletal variation and additional trabecular dilation it is difficult to recognize taxonomically relevant characters and to separate those from ecologically induced modifications. The high variability is probably related to radiations following phases of sea level rise and is connected to bioevents. Length of major septa in ontogenetic stages allows a separation of different populations within the Macgeea dubia species group. However, it remains questionable if septal length is a reliable taxonomic character, indicating a phylogenetic trend, or if it is subject to large individual variability. By revising Macgeea dubia, we reveal its synonymy with Macgeea heterophylloides sensu Birenheide. In addition, Macgeea recta (type species of Pexiphyllum Walther, 1929) is discussed as an insufficiently defined taxon of problematic status. Macgeea crassiseptata n. sp. is also described from the Late Givetian of Morocco. The erection of the new pseudocolumellate genus Baculophyllum with type species Pexiphyllum ultimum Walther, 1929 requires a comparison with Protomacgeea from Poland and Australia as well as a phylogenetic discussion of the solitary Phillipsastreidae. The new genus most probably belongs to a separate lineage of the Upper Devonian Macgeea group but could also be considered as a descendant of the Australian Lower Devonian columellate solitary phillipsastreid species group, that has not yet been recorded from the Middle Devonian. Because of large stratigraphic gaps between the occurrences of both genera, preference is given to the interpretation of a development of polycronomorph taxa (homeomorphic taxa living at a different time) not belonging to a single lineage. This shows again the significance of stratigraphic age when comparing similar-looking taxa, which should be considered in any phylogenetic reconstruction.